Comparative Evaluation of Internal Fit and Marginal Fit of Zirconia Copings Obtained From Impression and Die Fabricated using CAD-CAM an In Vitro Study - Tamizhesai Balavadivel1 , Raghavendra Jayesh2 , Sanjna Nayar3 , Venkateshwaran Rajendran4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aims: To evaluate and compare the internal fit and marginal fit of zirconia copings fabricated using CADCAM from impressions and model.Material and Methods: Using a standardized die, 15 impressions group 1and 15 models group 2 weremade with standardized protocol. All impressions and models were scanned and virtual models were made.Using the CAD data, zirconia copings were fabricated and cemented using silicone under finger pressureand standardized sections of the silicone were made and thicknesses were measured at eleven specific pointsunder stereomicroscope.Statistical analysis used: ANOVAResults: Mean Internal gap value of Group 1was 292.4µ ± 23.48 and Group 2 was 258.54 µ ± 22.83 µ, MeanMarginal Gap value of group1 was 252.64µ ± 11.86 µ and group2 was 232.18 µ ± 06.24 µ, ANOVA testshowed statistical significance with p value >0.05Conclusions: Within the limitations of the study, mean marginal gaps of both the groups were withinclinically acceptable range. Group 2 copings demonstrated comparatively smaller values. Hence fit of therestoration is better in Group 2 (copings fabricated from scanned models)